Maternal Practices and Stunting Prevention Among Toddlers: A Study in Wara Health Center, Palopo City, 2025 - Kaharuddin, Nur Wildah; Sastria, Andi; Asriadi, Asriadi; Amanah, Indra (AACENDIKIA: Journal of Nursing, 2025)
Stunting is a condition in which the growth and development of toddlers are delayed due to chronic malnutrition, resulting in height that is not appropriate for age. Stunting remains a significant public health issue globally, nationally, and locally, with concerning prevalence rates despite a gradual decline in recent years. Mothers play a crucial role in stunting prevention, as they are the primary caregivers of toddlers. Inadequate maternal practices may increase the risk of stunting. This study aimed to determine the relationship between maternal knowledge, attitudes, and the role of posyandu (integrated health post) cadres and maternal practices in stunting prevention among toddlers in the working area of Wara Public Health Center, Palopo City, in 2025. This quantitative study used a descriptive analytic design with a cross-sectional approach. A total of 83 respondents were selected using purposive sampling. Data were analyzed using the Chi-Square test. The results showed significant relationships between maternal knowledge (p = 0.018), attitudes (p = 0.016), and the role of posyandu cadres (p = 0.040) with maternal practices in preventing stunting. These findings indicate that knowledge, attitude, and the support of posyandu cadres are important factors influencing maternal efforts to prevent stunting in toddlers.